Menschenrechte, Geschlecht, Religion: Das Problem der Universalität und der Fähigkeitenansatz von Martha Nussbaum - Mügge, Cornelia (transcript, 2017)
How are universal norms established? Cornelia Mügge, in discussions with Martha Nussbaum, looks for an answer that convincingly incorporates the current social controversies surrounding women's rights and religious freedom.